Interventions for family members or caregivers of patients taking part in a cardiac rehabilitation program - Loureiro, Maria (2021)
Introduction: Cardiac Rehabilitation (CR) is a multifactorial program, usually composed of structured physical exercise, psychological support and education to promote positive changes in the lifestyle of people with different heart diseases. Most studies define that it is important to involve the family (caregivers) after the diagnosis of heart disease to guarantee the treatment's success, and CR is no different. Not being an implicit objective of secondary prevention of CR, some of the interventions included in CR can positively impact caregivers. Therefore, it is essential to understand which interventions can be used to promote the role of caregiver and their health. Objective: Map which interventions have been implemented that support caregivers of patients with the cardiac disease taking part in a cardiac rehabilitation program, in their role and health. Methods: Scoping Review guided by the methodology proposed by the Joanna Briggs Institute for conducting Scoping Reviews. Two independent reviewers will evaluate the relevance of the articles, the extraction and synthesis of the data. Studies written in English, Spanish and Portuguese, published after 1950, will be considered for inclusion in this review, researched in the following bibliographic sources: CINAHL Complete (Via EBSCO); PubMed; Scopus; SciELO; Cochrane Library; Pedro; DART-Europe; OpenGrey and RCAAP . Results: With this scoping review, it's proposed to include several studies that unequivocally demonstrate the existence of interventions with a positive and facilitating impact on health and the role of caregivers of people with heart disease in CR programs. Conclusion: This systematic review protocol provides mapping interventions to the caregiver of people with heart disease, demonstrating the added value of being integrated into CR programs.